2017
DOI: 10.24200/imminv.v2i2.54
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of Multiple Sclerosis in East-Azerbaijan Province, Iran, 2014

Abstract: Background: Multiple sclerosis (MS) as a chronic disease of the central nervous system have the very prevalent in worldwide. Its epidemiology is different region by region, and most of the geographical and environmental factors may play a role in its incidence. We designed this study to analyze demographic characteristics of MS. Methods: This survey has been conducted in East-Azerbaijan province, northwest of Iran. Prevalence of the MS has been measured using data from Committee for Diagnosis and Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Finally, 39 articles (included 103 studies for prevalence and 34 studies for incidence) entered the meta-analysis process after qualitative assessment. The flow diagram of the identification and selection of studies is illustrated in (Fig 1) and the characteristics of studies are shown in (Table 1) [2, 5, 13, 25, 26, 3137, 39, 40, 42–46, 53–71].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 39 articles (included 103 studies for prevalence and 34 studies for incidence) entered the meta-analysis process after qualitative assessment. The flow diagram of the identification and selection of studies is illustrated in (Fig 1) and the characteristics of studies are shown in (Table 1) [2, 5, 13, 25, 26, 3137, 39, 40, 42–46, 53–71].…”
Section: Resultsmentioning
confidence: 99%
“…The results of a meta-analysis in 2020 demonstrated that during 1985–2018, the prevalence of the disease in Iran had increased by 2.30% annually [ 10 ]. Also, studies conducted in the country represented that the following provinces had the highest prevalence rates of MS: Tehran ( n = 148.06 per 100,000 in 2018) [ 11 ], Isfahan ( n = 85.80 per 100,000 in 2014) [ 12 ], and East Azerbaijan ( n = 73.26 per 100,000 in 2014) [ 13 ]. Besides, the results of a study conducted in Fars province in 2015 showed that this province had high prevalence and incidence rates among the provinces of the country, the former was 72.10 and the latter was 5.20 per 100,000 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%